PERANCANGAN SEKOLAH PENDIDIKAN ANAK USIA DINI DI KOTA MEDAN DENGAN PENDEKATAN ARSITEKTUR MODERN - Sihombing, Sanggam B.; Aritonang, Liesbeth; Yaputri, Angeline Maya (Jurnal Sains dan Teknologi ISTP, 2024)
Schools in Indonesia are conventional schools where students and teachers do activities which are commonly referred to as teaching and learning activities even though the school is not a place to lure students with stacks of information but also to train in terms of maturity of thinking and maturity of attitude.Along with the development of times, public awareness about the importance of education continues to increase. This also goes together with parents awareness to provide the best education for their children.Education for children certainly starts from informal education in family and then continues to formal education in school. Early childhood education is the main basis of education to the next levels. In Indonesia, the level of education participation in Kindergarten increases every year. But the number of kindergartens that have adequate facilities / infrastructure for learning / play tends to decrease every year. Early Childhood Education in the City of Medan is a place of care and education Children aged 6 months - 2 years, Class 2 to 4 years (Play Group) and 4 to age 6 years (Kindergarten)